Empowering Female Leadership and Cultivating a Digital Mindset: Enhancing Indonesia's Jamu MSMEs through Strategic SWOT Analysis - Khwarazmita, Tsabita; Churiyah, Madziatul (Sains Manajemen: Jurnal Manajemen Unsera, 2024)
Women's leadership is an integral part of the movement towards gender equality and the growth of MSMEs. It also plays a pivotal role in the comprehensive digitalization of businesses. This study provides a comprehensive analysis of MSMEs, examining internal and external factors, including strengths, weaknesses, opportunities, and threats, to identify the best strategy for growth. Our approach considers women's leadership and a digital mindset while developing the Jamu Oeti Malang MSME business. Primary data was obtained from interviews with MSMEs and further analyzed this data using SWOT analysis. The findings suggest that an offensive-expansion strategy would be most appropriate. Jamu Oeti MSMEs should expand their market while emphasizing women's leadership in business, pursuing continuous innovation, and supporting and utilizing digitalization by encouraging a workforce committed to technology. To achieve this, Jamu Oeti MSMEs can strengthen women's leadership and digital mindset through training and development programs, adopting and integrating technology, establishing strategic collaborations, focusing on sustainable innovation, and utilizing data for future business strategies. Kepemimpinan perempuan merupakan bagian integral dari gerakan menuju kesetaraan gender dan pertumbuhan UMKM. Hal ini juga memainkan peran penting dalam digitalisasi bisnis yang komprehensif. Studi ini memberikan analisis komprehensif terhadap UMKM, mengkaji faktor internal dan eksternal, termasuk kekuatan, kelemahan, peluang, dan ancaman, untuk mengidentifikasi strategi pertumbuhan terbaik. Pendekatan kami mempertimbangkan kepemimpinan perempuan dan pola pikir digital dalam mengembangkan bisnis UMKM Jamu Oeti Malang. Data primer diperoleh dari wawancara kepada UMKM dan selanjutnya data tersebut dianalisis dengan menggunakan analisis SWOT. Temuan ini menunjukkan bahwa strategi ekspansi ofensif adalah yang paling tepat. UMKM Jamu Oeti harus memperluas pasarnya dengan tetap mengedepankan kepemimpinan perempuan dalam bisnis, mengupayakan inovasi berkelanjutan, serta mendukung dan memanfaatkan digitalisasi dengan mendorong tenaga kerja yang berkomitmen terhadap teknologi. Untuk mencapai hal tersebut, UMKM Jamu Oeti dapat memperkuat kepemimpinan perempuan dan pola pikir digital melalui program pelatihan dan pengembangan, adopsi dan integrasi teknologi, menjalin kolaborasi strategis, fokus pada inovasi berkelanjutan, dan pemanfaatan data untuk strategi bisnis masa depan.